2005
DOI: 10.1681/asn.2004100885
|View full text |Cite
|
Sign up to set email alerts
|

Sevelamer Controls Parathyroid Hormone–Induced Bone Disease as Efficiently as Calcium Carbonate without Increasing Serum Calcium Levels during Therapy with Active Vitamin D Sterols

Abstract: Little is known about the impact of various phosphate binders on the skeletal lesions of secondary hyperparathyroidism (2°HPT). The effects of calcium carbonate (CaCO 3 ) and sevelamer were compared in pediatric peritoneal dialysis patients with bone biopsy-proven 2°HPT. Twenty-nine patients were randomly assigned to CaCO 3 (n ‫؍‬ 14) or sevelamer (n ‫؍‬ 15), concomitant with either intermittent doses of oral calcitriol or doxercalciferol for 8 mo, when bone biopsies were repeated. Serum phosphorus, calcium, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 47 publications
4
73
1
Order By: Relevance
“…The use of CART also identified the relationship between serum calcium concentrations and defective mineralization. Indeed, low serum calcium levels and high serum PTH values were the strongest predictors of mineralization defect in patients with bone turnover within the normal range, a finding that should be taken into consideration in view of the availability of therapeutic agents, such as calcium-free phosphate binders (10,27) and calcimimetic agents (28), which maintain serum calcium levels within the lower normal range. None of the patients included in this analysis received any of these agents before bone biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of CART also identified the relationship between serum calcium concentrations and defective mineralization. Indeed, low serum calcium levels and high serum PTH values were the strongest predictors of mineralization defect in patients with bone turnover within the normal range, a finding that should be taken into consideration in view of the availability of therapeutic agents, such as calcium-free phosphate binders (10,27) and calcimimetic agents (28), which maintain serum calcium levels within the lower normal range. None of the patients included in this analysis received any of these agents before bone biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…All of the subjects were part of various clinical investigations to characterize the spectrum of renal osteodys-trophy in pediatric dialysis patients (3,(7)(8)(9)(10)(11); only baseline biopsies were used for the current analysis. All patients received calcium-based phosphate binders at the time of the bone biopsy, and in those treated with daily oral calcitriol, such therapy was held for 4 weeks before bone biopsy.…”
Section: Methodsmentioning
confidence: 99%
“…The newer vitamin D analogues namely 22-oxacalcitriol, 19-nor-1, 25-dihydroxy vitamin D2 (paricalcitol) and 1α-hydroxyvitamin D2 (doxercalciferol) are associated with minimal intestinal calcium and phosphorus absorption. PTH levels are effectively reduced by doxercalciferol and paricalcitol; both have the ability to reduce serum calcium levels better than calcitriol in CKD children and adults [103,104] . Where SHPT is due to hyperphosphataemia, appropriate use of phosphate binders may just be sufficient.…”
Section: Shptmentioning
confidence: 99%
“…Secondary analyses of postmenopausal patients with osteoporosis and undiagnosed CKD in randomized, controlled trials of antiresorptive or anabolic agents show efficacy (55-58) compared with placebo (both the treatment and the placebo groups received calcium supplementation). Calcium-based phosphate binders (at doses generally greater than those used in placebo groups of osteoporosis trials) compared with non-calcium-containing phosphate binders did not show improvement in bone histology; some studies demonstrated the development of adynamic bone disease with calcium-based binders (12,(59)(60)(61)(62)(63); further reviewed in 36). No studies have shown that calcium supplement or binder intake improves bone mineral density.…”
Section: Efficacy Of Calcium Binders For Bone Health In the Ckd Populmentioning
confidence: 99%